Prevalence and intensity of soil-transmitted helminth infections in Uganda: Results from population-based prevalence surveys in five districts. - Benjamin Tinkitina; Prudence Beinamaryo; Moses Adriko; Betty Nabatte; Moses Arinaitwe; Alfred Mubangizi; Paul Emerson; Sanjaya Dhakal; Kristin M Sullivan (Public Library of Science (PLoS), 2023)
Background Soil-transmitted helminth (STH) infections are caused by roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), and hookworms (Necator americanus and Ancylostoma duodenale). In Uganda, baseline surveys conducted during the late 1990s and early 2000s suggested STH infections were common, with prevalence >50% among surveyed schoolchildren. In 2003, a national program was launched with mass preventative chemotherapy (PC) and health education for children 1-14 years old. Little evidence is available to show the impact of national deworming. Methods We conducted population-based, cross-sectional household surveys in five districts (Buikwe, Kassanda, Kiryandongo, Kisoro, and Rubanda) in March and May 2022. Our primary objective was to estimate STH prevalence by species due to infections of any intensity and infections of moderate-to-heavy intensity among preschool-aged children (PSAC, 1-4 years old), school-aged children (SAC, 5-14 years old), and women of reproductive age (WRA, 15-49 years old). Laboratory technicians used duplicate Kato-Katz microscopy to determine fecal egg count. Results Overall, 3,352 PSAC; 3,884 SAC; and 1,226 WRA provided stool samples. The prevalence of any infection remained high in Kisoro at or above ~50% within all risk groups. In other districts, the prevalence of any infection ranged from approximately 5 to 16% among PSAC, 6 to 23% among SAC, and 12 to 19% among WRA. Moderate-to-heavy intensity infection prevalence was highest in Kisoro (~15-26%), followed by Rubanda (<5%), and was ≤1% in other districts. A. lumbricoides and T. trichiura infections were largely confined to Kisoro and Rubanda, whereas hookworm was most common in other districts. Conclusions The STH prevalence has decreased markedly in three districts in Uganda. Based on our findings, the national deworming program should consider decreasing PC distribution frequency in these districts per the World Health Organization guidelines. Efforts are needed to understand why the Kisoro and Rubanda districts did not demonstrate similar gains.